The activities of current antimalarial drugs on the life cycle stages of Plasmodium: a comparative study with human and rodent parasites. - Michael Delves (Public Library of Science (PLoS), 2012)
Background Malaria remains a disease of devastating global impact, killing more than 800,000 people every year-the vast majority being children under the age of 5. While effective therapies are available, if malaria is to be eradicated a broader range of small molecule therapeutics that are able to target the liver and the transmissible sexual stages are required. These new medicines are needed both to meet the challenge of malaria eradication and to circumvent resistance. Methods and findings Little is known about the wider stage-specific activities of current antimalarials that were primarily designed to alleviate symptoms of malaria in the blood stage. To overcome this critical gap, we developed assays to measure activity of antimalarials against all life stages of malaria parasites, using a diverse set of human and nonhuman parasite species, including male gamete production (exflagellation) in Plasmodium falciparum, ookinete development in P. berghei, oocyst development in P. berghei and P. falciparum, and the liver stage of P. yoelii. We then compared 50 current and experimental antimalarials in these assays. We show that endoperoxides such as OZ439, a stable synthetic molecule currently in clinical phase IIa trials, are strong inhibitors of gametocyte maturation/gamete formation and impact sporogony; lumefantrine impairs development in the vector; and NPC-1161B, a new 8-aminoquinoline, inhibits sporogony. Conclusions These data enable objective comparisons of the strengths and weaknesses of each chemical class at targeting each stage of the lifecycle. Noting that the activities of many compounds lie within achievable blood concentrations, these results offer an invaluable guide to decisions regarding which drugs to combine in the next-generation of antimalarial drugs. This study might reveal the potential of life-cycle-wide analyses of drugs for other pathogens with complex life cycles.